Modeling of Radio-wave Propagation in Forest by the Method of Parabolic Equation - S. Mikhailov, M; S. Malevich, E; A. Permyakov, V (International Journal of Engineering and Technology, 2018)
The influence of forests on the propagation of radio waves is an actual topic of research stimulated by practical tasks related to the operation of various types of communication, radar, radio navigation, geodesy, and remote sensing of the earth's surface. The dependence of the electric field strength modulus of the source above the ground surface is studied in the presence of an obstacle in the form of a forest massif. The main attention is paid to the analysis of the field within the forest with various parameters and forms of forest canopy. A new approach to the task is proposed for the forms of forest canopy, taking into account the type of forest: deciduous, coniferous or mixed. The effective dielectric permittivity is used as a parameter for specifying a forest massif. The propagation of radio waves is calculated using the parabolic equation method for a two-dimensional space model. The implemented methodology allows calculating sanitary protection zones and zones of building restriction, planning to plant or cut down forests for planning the propagation of radio waves taking this into account.Â Â